Identification of a novel mutation at the primary dimer interface of GyrA conferring fluoroquinolone resistance in Clostridium difficile. Issue 4 (December 2015) - Mac Aogáin, Micheál; Kilkenny, Shauna; Walsh, Claire; Lindsay, Sinéad; Moloney, Geraldine; Morris, Trefor; Jones, Sophie; Rogers, Thomas R.
Graphical abstract: Highlights: First reported non-QRDR mutation conferring fluoroquinolone resistance in Clostridium difficile . GyrA Ala384Asp has a pleiotropic effect on resistance: fluoroquinolones + novobiocin. Extra-QRDR polymorphisms are present in fluoroquinolone-resistant isolates. Strains devoid of gyrBA polymorphisms exhibit DNA gyrase-independent resistance. In silico analysis revealed a diversity of extra-QRDR polymorphisms in DNA gyrase. Abstract: The aim of this study was to determine whether alternative resistance mechanisms, other than mutation in the quinolone resistance-determining region (QRDR) of DNA gyrase, could confer fluoroquinolone resistance in Clostridium difficile . An in vitro-generated C. difficile mutant exhibiting increased fluoroquinolone resistance was isolated through antibiotic selection on ciprofloxacin. The QRDR of this mutant was investigated by chain-termination sequencing and was found to be devoid of mutation. To determine the nature of the non-QRDR resistance mechanism in this strain, the genomes of the mutant and wild-type strains were sequenced. The gyrBA region from a collection of clinical isolates exhibiting variable fluoroquinolone resistance levels was also sequenced and was compared with that present in 918 publicly available C. difficile genomic data sets. Whole-genome sequence analysis of the fluoroquinolone-resistant mutant revealed a single non-synonymous substitution (Ala384Asp) at the predicted primary dimer interface of GyrA, far beyond the classically defined QRDR. This novel mutation caused increased resistance to ciprofloxacin, ofloxacin, levofloxacin and moxifloxacin while conferring hypersusceptibility to novobiocin. Several novel extra-QRDR polymorphisms in C. difficile DNA gyrase were identified among clinical isolates, whilst observed fluoroquinolone resistance in strains devoid of gyrBA mutations confirmed the existence of DNA gyrase-independent resistance mechanisms in this species. In conclusion, we report the first non-QRDR mutation to confer fluoroquinolone resistance in C. difficile. Although the Ala384Asp substitution was not detected in clinical isolates, this study revealed a diversity of alternative extra-QRDR polymorphisms in DNA gyrase whose association with fluoroquinolone resistance warrants further investigation.